2022
DOI: 10.30935/cedtech/11476
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Social Media as a Tool for Learning: Perspectives of Students in the Faculty of Education at Kuwait University

Abstract: The purpose of this study is to explore the use of social media by students in the Faculty of Education, University of Kuwait. The study was conducted within the context of the socio-cultural characteristics of Kuwait, and was underpinned by Alsaied's (2017) Social Media -Learning Performance model, designed for female Arab students. A volunteer sample of 35 Kuwaiti undergraduate students (88.6% female) was interviewed. Students reported frequently using social media informally for socialization and entertainm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…Different types of social media have been used in teaching, including Twitter, WhatsApp, Instagram, YouTube, and Snapchat ( Alenezi and Brinthaupt, 2022 ; Noori et al, 2022 ). Research indicates that students have specific preference for the type of social media they use to support their learning ( Ma et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Different types of social media have been used in teaching, including Twitter, WhatsApp, Instagram, YouTube, and Snapchat ( Alenezi and Brinthaupt, 2022 ; Noori et al, 2022 ). Research indicates that students have specific preference for the type of social media they use to support their learning ( Ma et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Millions of people around the world use social media applications for a variety of reasons and on a regular basis (Al-Rahmi et al, 2014). The widespread use of social media applications by students has contributed to their rapid acceptance (Kirschner & Karpinski, 2010;Alenezi & Brinthaupt, 2022). This implies that the Buhare CDTI students, like any other students worldwide, were well exposed to social media networks, as the majority of them reported using various social media platforms for both academic and communication purposes.…”
Section: Uses Of Social Media By Cdti Studentsmentioning
confidence: 99%
“…The study findings are further in line with those by Olipas (2022) who reported that students' social media use was also high in terms of entertainment and socialization, communication, and academic purposes. However, according to Alenezi and Brinthaupt's (2022) research, students use social media informally for socialization and entertainment, but less frequently as a formal educational tool.…”
Section: Uses Of Social Media By Cdti Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of media (especially modern media) does not ensure that teachers in elementary schools are motivated to use them. On the other hand, teachers' mental burden from being unable to use them is much greater and they do not search for a solution [7,12,13]. A number of other problems were found namely the use of learning media technology that was less than optimal due to a lack of components, poor quality and students' disinterest in media technology.…”
Section: Introductionmentioning
confidence: 99%